Gradient phenomenon of multidrug resistance gene expression in breast cancer during neoadjuvant chemotherapy is related to disease progression - N. V. Litviakov (Сибирский онкологический журнал)
The paper examined 106 patients with breast cancer (BC) treated with neoadjuvant chemotherapy (NАС). In the biopsy material, derived from primary tumor before NAC and surgical samples after chemotherapy the expression of 8 multidrug resistance genes (MDR) ABCB1, АВСВ2, ABCC1, ABCC2, АВСС5, ABCG1, ABCG2 и MVP was evaluated using quantitative RT-PCR. During the NAC course 75 % of patients manifested gradient phenomenon for gene expression that means a unidirectional change in the expression of all five MDR genes ABCB1, ABCC1, ABCC2, ABCG1 и ABCG2 closely associated with the NAC efficacy: the reduction in MDR gene expression was related to good response to NAC while the expression increase associated with poor response to NAC. In 25% of patients there was no such change in studied gene expression that means the lack of a gradient phenomenon. The objective was to study whether gradient phenomenon for MDR gene expression during NAC is related to disease free survival in breast cancer patients. Five-year metastasis-free survival in patients having a gradient phenomenon was 73 % versus 39 % in patients who lack a gradient phenomenon (log-rank test p=0,0018). So, the presence of a gradient phenomenon in patients is appeared to be associated with a good disease prognosis. It is assumed that the gradiThe paper examined 106 patients with breast cancer (BC) treated with neoadjuvant chemotherapy (NАС). In the biopsy material, derived from primary tumor before NAC and surgical samples after chemotherapy the expression of 8 multidrug resistance genes (MDR) ABCB1, АВСВ2, ABCC1, ABCC2, АВСС5, ABCG1, ABCG2 и MVP was evaluated using quantitative RT-PCR. During the NAC course 75 % of patients manifested gradient phenomenon for gene expression that means a unidirectional change in the expression of all five MDR genes ABCB1, ABCC1, ABCC2, ABCG1 и ABCG2 closely associated with the NAC efficacy: the reduction in MDR gene expression was related to good response to NAC while the expression increase associated with poor response to NAC. In 25% of patients there was no such change in studied gene expression that means the lack of a gradient phenomenon. The objective was to study whether gradient phenomenon for MDR gene expression during NAC is related to disease free survival in breast cancer patients. Five-year metastasis-free survival in patients having a gradient phenomenon was 73 % versus 39 % in patients who lack a gradient phenomenon (log-rank test p=0,0018). So, the presence of a gradient phenomenon in patients is appeared to be associated with a good disease prognosis. It is assumed that the gradient phenomenon is the marker indicating the presence of a balanced system of gene regulation and tumor cell response to chemotherapy. Practically, the estimation of the effectiveness of preoperative chemotherapy along with a change in MDR gene expression during NAC could significantly improve prediction of disease outcome in patients with breast cancer.